Preparation method of microcrystalline glass
By quenching, alkali activation and mechanical foaming of coal gasified ash slag, the problems of high energy consumption and difficulty in regulating pore structure in the treatment of coal gasified ash slag are solved, and the resource utilization and microcrystalline of coal gasified ash are realized. Efficient preparation of glass.
Patent Information
- Application Number
- CN202310790646.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the treatment of coal gasified ash slag has problems such as high energy consumption and difficulty in regulating the pore structure, resulting in waste of land resources and environmental pollution, and it is difficult to achieve large-scale treatment.
By quenching the coal gasified ash slag in molten water, alkali activation, precuring and mechanical foaming are carried out to form an inorganic gel, and then cured in the mold and sintered to obtain microcrystalline glass with rich pore structure.
The resource utilization of coal gasified ash slag is realized, the sintering temperature and energy consumption are reduced, and the pore structure and crystal phase can be effectively regulated, and the quality and performance of crystallized glass are improved.
Smart Images

Figure CN119219336A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of solid waste resource utilization, and in particular, to a method for preparing microcrystalline glass. Background Art
[0002] The coal gasification process is the core technology for the clean and efficient utilization of coal resources. A certain proportion of gasification ash will be produced during the coal gasification process, and the output and reserves of gasification ash are also gradually increasing with the continuous expansion of production capacity. However, the huge amount of gasification ash cannot be effectively utilized, resulting in waste of land resources and serious environmental pollution. The disposal of gasification ash has become one of the key issues restricting the large-scale utilization of coal gasification technology. Gasification ash is rich in silicon, aluminum and other elements, and has abundant mineral resources. Completing the transformation of minerals in gasification ash into resource materials and realizing the resource utilization of waste are effective measures to solve the problem of large-scale treatment and application of gasification ash and promote the sustainable development of coal chemical enterprises.
[0003] In the prior art, there is a method for preparing foamed microcrystalline glass using secondary aluminum ash. Based on the particle-stabilized foam theory, the calcined secondary aluminum ash and waste glass are mixed evenly, and then water and a surface modifier are added to obtain a solid-liquid mixed phase slurry. The slurry is stirred and foamed to obtain a particle-stabilized foam, and finally injection molding, demolding, drying, and sintering are performed to obtain foamed microcrystalline glass. An additional 10 to 70% of waste glass needs to be added to supplement the required glass network former. The secondary aluminum ash and waste glass particles are hydrophobically modified by a surface modifier. Based on the particle-stabilized foam theory, it is difficult to regulate the pore structure in the foamed microcrystalline glass by direct foaming using mechanical stirring. The calcination temperature of the foamed dry blank needs to be between 1000 and 1200°C, the sintering temperature is high, and the energy consumption is large. Therefore, it is necessary to develop a short-process, low-energy method for preparing microcrystalline glass using gasified slag to effectively gasify the ash and realize the resource utilization of waste. Summary of the invention
[0004] In view of this, the present disclosure provides a method for preparing microcrystalline glass to at least partially solve the above technical problems.
[0005] In order to solve the above technical problems, the technical solutions provided by the present disclosure are as follows:
[0006] According to an embodiment of the present disclosure, a method for preparing glass-ceramics is provided, comprising:
[0007] The coal gasification ash is quenched with molten water to obtain glass phase slag;
[0008] performing an alkali activation treatment on the glass phase slag to obtain a monomer suspension containing a predetermined type of monomer;
[0009] Pre-curing the monomer suspension to obtain an inorganic gel;
[0010] Performing mechanical foaming treatment on the inorganic gel to obtain a foamed gel;
[0011] Putting the foaming gel into the mold and curing the foaming gel under predetermined curing conditions to obtain a foamed glass embryo;
[0012] The foam glass embryo is sintered to obtain glass-ceramics.
[0013] According to an embodiment of the present disclosure, the alkali activation treatment of the glass phase slag includes:
[0014] The glassy slag is placed in an alkali-activated solution, so that part of the glassy slag undergoes a hydration reaction in the alkali-activated solution to generate a monomer suspension, wherein the monomer suspension includes a predetermined type of monomers and unreacted slag particles.
[0015] According to an embodiment of the present disclosure, wherein:
[0016] The alkaline excitation solution uses a NaOH aqueous solution;
[0017] The predetermined types of monomers include at least: calcium aluminosilicate hydrate monomers and sodium aluminosilicate hydrate monomers.
[0018] According to an embodiment of the present disclosure, after placing the glass phase slag in an alkali-activated solution, the process further comprises:
[0019] The base-activated solution is stirred under first predetermined stirring conditions.
[0020] According to an embodiment of the present disclosure, the first predetermined stirring condition includes:
[0021] The first stirring speed is: 300-500 rpm
[0022] The first stirring time is: 1 to 4 hours
[0023] According to an embodiment of the present disclosure, pre-curing the monomer suspension includes:
[0024] The monomer suspension is placed in a drying oven, and a predetermined type of monomer in the monomer suspension is subjected to a polycondensation reaction under predetermined curing conditions to generate a polycondensate, and the unreacted slag particles are wrapped by the polycondensate to obtain an inorganic gel.
[0025] According to an embodiment of the present disclosure, the predetermined curing conditions include:
[0026] Curing temperature: 70~80℃
[0027] Curing time: 30 to 120 minutes.
[0028] According to an embodiment of the present disclosure, the inorganic gel is subjected to mechanical foaming treatment to obtain the foamed gel, which comprises:
[0029] A surfactant is added to the inorganic gel, and the inorganic gel and the surfactant are mixed under a second predetermined stirring condition, so that the inorganic gel is mechanically foamed under the stirring action and the action of the surfactant to obtain a foamed gel.
[0030] According to an embodiment of the present disclosure, wherein:
[0031] The surfactant used is polyethylene glycol octylphenyl ether.
[0032] According to an embodiment of the present disclosure, the second predetermined stirring condition includes:
[0033] The second stirring speed is: 2000-2500 rpm;
[0034] The second stirring time is: 10 to 20 minutes;
[0035] According to an embodiment of the present disclosure, wherein:
[0036] The mass contents of glass phase slag, alkali activated solution and surfactant are:
[0037] Glass phase slag: 51~66Wt%;
[0038] Alkali excitation solution: 30-45Wt%;
[0039] Surfactant: 3-5 wt%.
[0040] According to an embodiment of the present disclosure, sintering the foam glass embryo to obtain glass-ceramics includes:
[0041] Heating the foam glass embryo to a predetermined sintering temperature at a predetermined heating rate;
[0042] The glass-ceramics is obtained by sintering the foam glass embryo body according to a predetermined sintering temperature.
[0043] According to an embodiment of the present disclosure, wherein:
[0044] The predetermined heating rate is: 5-20°C / min;
[0045] The predetermined sintering temperature is: 700~1000℃;
[0046] According to an embodiment of the present disclosure, the predetermined maintenance conditions include:
[0047] Curing temperature: 70~80℃;
[0048] The curing time is: 12 to 48 hours.
[0049] According to an embodiment of the present disclosure, wherein:
[0050] The components of coal gasification ash include at least one of the following: SiO2, Al2O3, CaO, Fe2O3.
[0051] According to an embodiment of the present disclosure, wherein:
[0052] In the glassy slag, the content of glassy substances is greater than 95%.
[0053] According to an embodiment of the present disclosure, before the glass phase slag is subjected to alkali activation treatment, the process further includes:
[0054] The glassy slag is ground.
[0055] According to an embodiment of the present disclosure, wherein:
[0056] The particle size of the glassy slag obtained after grinding is less than 75 μm.
[0057] Based on the above technical solution, the method for preparing glass-ceramics provided by the present disclosure has at least the following beneficial effects:
[0058] (1) In the embodiments of the present disclosure, the minerals in the coal gasification ash are completely melted into a liquid melt in a melting furnace by molten water quenching, and then the melt discharged in liquid form is water quenched to inhibit the precipitation of crystals in the melt, thereby forming a glass phase slag rich in silicon and aluminum elements.
[0059] (2) In the embodiments of the present disclosure, the glass phase slag can be directly subjected to alkali activation treatment without the need to add waste glass or perform vitrification treatment. The alkali activation treatment of the glass phase slag using an alkali activated solution can promote the hydration reaction between the glass phase in the slag and the alkali activated solution and generate a monomer suspension.
[0060] (3) In the embodiments of the present disclosure, the monomer suspension undergoes a condensation reaction during the pre-curing treatment stage to encapsulate the undissolved particles to form an inorganic gel system; the inorganic gel is then subjected to a mechanical foaming treatment, and air is encapsulated into the organic gel to form a large amount of foam during the vigorous stirring process. Compared with the use of a foaming agent for high-temperature in-situ reaction foaming, this avoids the problem of difficult regulation of the three phases of gas phase, crystal phase and glass phase at high temperature, and is conducive to directional regulation of the pore structure and crystal phase to obtain products with specific required performance.
[0061] (4) In the embodiments of the present disclosure, the foaming treatment and the sintering treatment processes are separated, which is convenient for the individual regulation of the processes. The sintering treatment of the foam glass embryo is helpful to remove the bound water and OH generated during the polycondensation process, and secondary foaming occurs to form bubbles with smaller porosity. At the same time, the pore structure generated by mechanical foaming is stabilized to obtain microcrystalline glass with rich pore structure.
[0062] (5) In the embodiments of the present disclosure, the organic carbon in the gasification ash is fully converted and utilized through the fluidized melting combustion process to form a glass phase slag, and the slag is prepared into foam microcrystalline glass in combination with the inorganic gel casting process. The process has strong operability and makes full use of the activation and modification of minerals in the coal gasification ash by the melting process, thereby realizing the resource utilization of minerals in the coal gasification ash. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 is a schematic diagram of the operation flow of a method for preparing glass-ceramics according to an embodiment of the present disclosure;
[0064] Figure 2 It is a schematic diagram of the operation flow of a method for preparing microcrystalline glass according to another embodiment of the present disclosure. DETAILED DESCRIPTION
[0065] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0066] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.
[0067] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0068] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art, unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification, and should not be interpreted in an idealized or overly rigid manner.
[0069] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).
[0070] At present, the treatment methods of coal gasification ash are mainly storage and landfill, which has not been applied on a large scale in industry, causing serious environmental pollution and waste of land resources, and adversely affecting the sustainable development of coal chemical enterprises. Large-scale treatment of coal gasification ash is imminent. In the process of realizing the present disclosure, it is found that waste glass, fly ash, smelting slag, etc. are used as the main raw materials, and then a foaming agent, a flux, etc. are added. After crushing and mixing, a porous microcrystalline glass material can be made after sintering and other heat treatments, but there are problems such as a long process, a high sintering temperature, and a large energy consumption.
[0071] In view of this, the present disclosure provides a method for preparing microcrystalline glass. Figure 1 FIG. 1 is a schematic diagram of the operation flow of a method for preparing glass-ceramics according to an embodiment of the present disclosure. Figure 1 As shown, the preparation method of the microcrystalline glass includes:
[0072] The coal gasification ash is quenched with molten water to obtain glass phase slag;
[0073] performing an alkali activation treatment on the glass phase slag to obtain a monomer suspension containing a predetermined type of monomer;
[0074] Pre-curing the monomer suspension to obtain an inorganic gel;
[0075] Performing mechanical foaming treatment on the inorganic gel to obtain a foamed gel;
[0076] Putting the foaming gel into the mold and curing the foaming gel under predetermined curing conditions to obtain a foamed glass embryo;
[0077] The foam glass embryo is sintered to obtain glass-ceramics.
[0078] In the process of incomplete combustion of coal and oxygen or oxygen-enriched air to produce CO and H2, the inorganic minerals in the coal undergo different physical and chemical transformations to form solid gasification ash accompanied by residual carbon particles in the coal. The composition of the gasification ash is related to the ash content, composition and gasification process of the gasification raw coal, and contains elements such as silicon and aluminum, mainly SiO2, Al2O3, CaO and residual carbon.
[0079] According to an embodiment of the present disclosure, in the above-mentioned method for preparing glass-ceramics, during the process of subjecting the coal gasification ash to molten water quenching treatment, an ultra-low volatile carbon-based fuel is fed into a melting treatment device to obtain glass-phase slag. Specifically, the coal gasification ash containing silicon and aluminum elements is subjected to a high-temperature melting treatment in a melting furnace to form a liquid solution, and then the liquid melt is subjected to a water quenching treatment to inhibit the precipitation of crystals to obtain a solid slag rich in glass phase. In addition to the coal gasification ash, the raw materials used may also be other solid wastes rich in silicon and aluminum element glass phase. Furthermore, the coal gasification slag is prepared into glass-ceramics through an inorganic gel casting process.
[0080] The glassy slag is rich in silicon and aluminum elements and has high activity, which can be activated by an alkali-activated solution to undergo a hydration reaction. The alkali-activated solution is an alkaline solution, including a strong alkaline solution and / or a weak alkaline solution, and its concentration can be adjusted according to actual conditions. When the glassy slag is subjected to an alkali-activated treatment using an alkaline solution, the alkaline solution partially dissolves and depolymerizes the aluminosilicate structure in the slag into monomers, and the formed monomers are silicate hydration products, which constitute a monomer suspension.
[0081] The monomer suspension containing silicate hydration products is pre-cured under predetermined curing conditions. The researchers pre-set the curing temperature and curing time in the predetermined curing conditions according to actual conditions. The pre-curing treatment is performed to expel the volatile substances in the monomer suspension, and a condensation reaction occurs to cause the monomers to condense with each other to form a polymer compound, and to wrap the undissolved particles. The liquid suspension is cured at a certain temperature to form a gel-state inorganic gel system.
[0082] Add nonionic surfactant to the inorganic gel system for vigorous mechanical stirring. During the vigorous stirring process, the first foaming is carried out to wrap air into the gel to form foam in the gel. At the same time, the nonionic surfactant is adsorbed on the gas-liquid interface to inhibit foam rupture, forming a large amount of foam in the inorganic gel, and a higher porosity can be obtained. Mechanical foaming is conducive to the directional regulation of pore structure and crystal phase. The stirring speed or stirring time of mechanical foaming can be adjusted according to the properties of the desired product to obtain products with specific properties.
[0083] The foamed gel is injected into the mold, placed in a drying oven and cured under predetermined curing conditions. The curing temperature and curing time are pre-set according to actual conditions. After the curing is completed, the mold is demoulded to obtain a formed foam glass embryo.
[0084] The foam glass embryo is sintered to promote the precipitation of crystals, and the resulting microcrystalline glass has a rich pore structure. The sintering treatment stabilizes the pore structure generated during the mechanical foaming process, and removes the bound water and OH generated by the polycondensation reaction in the precuring stage under the high temperature of the sintering treatment, and secondary foaming occurs to form a smaller pore structure. Mechanical foaming treatment (first foaming) through inorganic gel combined with secondary foaming during the sintering process can make the pore structure in the microcrystalline glass richer and improve the quality of the microcrystalline glass. The mechanical foaming process is separated from the sintering process, avoiding the problem of difficult regulation of the gas phase, crystal phase and glass phase at high temperature. The sintering temperature requirement is low, which effectively reduces energy consumption.
[0085] According to an embodiment of the present disclosure, alkali activation treatment of glass phase slag includes: placing the glass phase slag in an alkali-activated solution so that part of the glass phase slag undergoes a hydration reaction in the alkali-activated solution to generate a monomer suspension, wherein the monomer suspension includes predetermined types of monomers and unreacted slag particles.
[0086] According to the embodiments of the present disclosure, since the glassy phase slag is rich in silicon and aluminum elements, it can be directly activated by an alkali-activated solution without vitrification treatment or the addition of waste glass. The characteristics of the slag being rich in silicon and aluminum elements are fully utilized, and an alkali-activated solution is used to activate it. The alkali activator can be selected from sodium hydroxide, potassium hydroxide, silicates, aluminates, phosphates, sulfates, carbonates and other substances containing alkaline elements. The alkali-activated solution accelerates the hydration reaction rate of the slag, and partially dissolves and depolymerizes the three-dimensional network structure of the silicate aluminate in the glassy phase slag into hydrated compound monomers.
[0087] According to an embodiment of the present disclosure, the alkaline excitation solution is a NaOH aqueous solution.
[0088] The predetermined types of monomers include at least: calcium aluminosilicate hydrate monomers and sodium aluminosilicate hydrate monomers.
[0089] According to the embodiments of the present disclosure, the alkali activating solution uses a NaOH aqueous solution, and the concentration of the NaOH aqueous solution can be adjusted as needed. The alkali content in the activator can improve the compressive strength of the material. The glass phase slag rich in aluminosilicate is dissolved and depolymerized using the NaOH aqueous solution to form a three-dimensional skeleton structure compound composed of silicon oxygen and aluminum oxygen tetrahedrons, such as hydrated calcium aluminosilicate and hydrated sodium aluminosilicate monomers, but it is not limited to the listed monomers.
[0090] According to an embodiment of the present disclosure, after placing the glass phase slag in the alkali-activated solution, the method further includes: stirring the alkali-activated solution under a first predetermined stirring condition.
[0091] According to an embodiment of the present disclosure, the first predetermined stirring condition includes:
[0092] The first stirring speed is: 300-500 rpm, for example, 350 rpm, 400 rpm, 500 rpm, etc.;
[0093] The first stirring time is 1 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0094] According to the embodiments of the present disclosure, after the glass phase slag is crushed, ground and screened, the powdered glass phase slag is mixed with an alkali-activated solution in a certain proportion, and stirred at a low speed on a mechanical stirrer under a first predetermined stirring condition, so that the glass phase slag is dispersed more evenly in the alkali-activated solution, and the glass phase in the slag and the alkali-activated solution are fully hydrated. The stirring speed of the first predetermined stirring condition should not be too high or too low. When the first stirring speed is too low, the glass phase slag cannot be fully dispersed in the alkali-activated solution, and the materials are unevenly mixed, which is not conducive to the full progress of the hydration reaction; when the first stirring speed is too high, the reaction phenomenon is fast, which will lead to uneven reaction.
[0095] According to an embodiment of the present disclosure, pre-curing treatment of the monomer suspension includes: placing the monomer suspension in a drying oven, causing predetermined types of monomers in the monomer suspension to undergo condensation polymerization under predetermined curing conditions to generate condensation polymers, and wrapping unreacted slag particles with the condensation polymers to obtain an inorganic gel.
[0096] According to the embodiments of the present disclosure, a monomer suspension containing monomers such as calcium aluminosilicate hydrate and sodium aluminosilicate hydrate is pre-cured to promote condensation polymerization of the monomers in the monomer suspension. The monomer suspension is placed in a drying oven, and the curing temperature and curing time are pre-set. The monomers are reacted at a predetermined temperature for a certain period of time to condense and polymerize with each other to form condensation compounds, and the unreacted slag particles are wrapped to form an inorganic gel system.
[0097] According to the embodiments of the present disclosure, during the pre-curing process, the curing temperature is 70-80°C, for example, it can be 72°C, 75°C, 78°C, etc.; the curing time is 12-48 hours, for example, it can be 12 hours, 24 hours, 36 hours, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0098] According to the embodiments of the present disclosure, the curing temperature should not be too high and should be kept uniform to prevent uneven heating, so that the curing temperature and curing time are adapted to each other, and the curing time is appropriately shortened when the curing temperature is high, and appropriately extended when the curing temperature is low. If the curing temperature is too high or the curing time is too long, the reaction mechanism will change and the gel will be too hard or aged; if the curing temperature is too high or the curing time is too short, the monomer suspension will not be completely cured, affecting the curing effect.
[0099] According to an embodiment of the present disclosure, the inorganic gel is subjected to mechanical foaming treatment to obtain the foamed gel, which includes: adding a surfactant to the inorganic gel, and mixing the inorganic gel and the surfactant under a second predetermined stirring condition, so that the inorganic gel is mechanically foamed under the stirring action and the action of the surfactant to obtain the foamed gel.
[0100] According to the embodiments of the present disclosure, a surfactant is added to the inorganic gel, and mechanical stirring is performed at a relatively high stirring rate. During the violent stirring process, air is encapsulated into the gel system to form foam. The addition of the surfactant inhibits the foam from bursting. The surfactant is adsorbed on the gas-liquid interface, and the hydrophobic part is excluded from the solvent. The hydrophilic part remains in the contraction structure with the liquid, inhibiting the liquid from flowing out of the foam film, thereby inhibiting the foam from bursting, and obtaining a foaming gel with rich pore structure. In addition, by adjusting the stirring speed and stirring time of the mechanical foaming, the pore structure and crystal phase can be directionally regulated, avoiding the problem that the three phases of gas phase, crystal phase and glass phase are difficult to regulate at high temperature during the high-temperature in-situ foaming process.
[0101] According to the embodiments of the present disclosure, the surfactant is a nonionic surfactant, which does not generate ions in water, avoids reacting with compounds in the glass phase slag to affect the foaming effect, and has the function of stabilizing the foam. The nonionic surfactant can be polyethylene glycol octylphenyl ether, which can stabilize the foam structure under mild conditions, and other nonionic surfactants that can maintain the foam morphology in the foaming gel can also be selected.
[0102] According to an embodiment of the present disclosure, the second predetermined stirring condition includes:
[0103] The second stirring speed is: 2000-2500 rpm, for example, 2000 rpm, 2200 rpm, 2300 rpm, etc. The second stirring time is: 10-20 minutes, for example, 10 minutes, 15 minutes, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The second predetermined stirring condition is high-speed mechanical stirring. High-speed and vigorous stirring of the gel helps to encapsulate more air in the gel system and form a large number of uniform bubbles.
[0104] According to the embodiments of the present disclosure, the mass contents of the glass phase slag, the alkali activated solution, and the surfactant are respectively:
[0105] Glass phase slag: 51-66 wt%, for example, 56 wt%, 61 wt%, etc.;
[0106] Alkali excitation solution: 30-45 wt%, for example, 35 wt%, 40 wt%, etc.;
[0107] Surfactant: 3-5 wt%, for example, 4 wt%, 4.5 wt%. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0108] According to an embodiment of the present disclosure, sintering a foam glass embryo to obtain a microcrystalline glass includes: heating the foam glass embryo to a predetermined sintering temperature at a predetermined heating rate; sintering the foam glass embryo at the predetermined sintering temperature to obtain the microcrystalline glass. The prepared microcrystalline glass can be used for thermal insulation materials or catalyst carriers.
[0109] According to the embodiments of the present disclosure, when the foam glass embryo is sintered, the bound water and OH generated by the condensation reaction during the pre-curing treatment can be removed under high temperature conditions, thereby causing secondary foaming to form a pore structure with smaller pores. At the same time, the larger pore structure produced by mechanical foaming is stabilized, and the Fe element and the like that are not dissolved during the sintering process serve as crystal nuclei, which promotes the precipitation of crystals, thereby obtaining microcrystalline glass with a rich pore structure.
[0110] According to an embodiment of the present disclosure, the predetermined heating rate is: 5 to 20°C / minute, for example, it can be 10°C / minute, 15°C / minute, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0111] The predetermined heating rate has a significant impact on the structure and properties of the microcrystalline glass. When the heating rate is lower than 5°C / min, the heating time is long, the energy consumption is high, and the production efficiency is low. When the heating rate is higher than 20°C / min, it is easy to cause the microcrystalline glass after sintering and crystallization treatment to have poor crystal development and large spatial dislocation defects, resulting in reduced volume density and product deformation and cracking.
[0112] According to an embodiment of the present disclosure, the predetermined sintering temperature is: 700-1000°C / min, for example, it can be 700°C, 800°C, 900°C, 1000°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0113] When the predetermined sintering temperature is low, the crystals of the microcrystalline glass develop and grow slowly, the crystal phase transition is incomplete, the volume density of the product after sintering and crystallization treatment is low, and the bending and compressive strengths are low; when the predetermined sintering temperature is high, the sintering and crystallization treatment temperature will cause the microcrystalline glass product to soften and deform, and generate greater energy consumption.
[0114] According to an embodiment of the present disclosure, when the foaming gel is placed in a mold and cured under predetermined curing conditions, the predetermined curing conditions include:
[0115] Curing temperature: 70~80℃
[0116] The curing time is 12 to 48 hours, for example, 12 hours, 24 hours, 36 hours, 48 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0117] According to an embodiment of the present disclosure, the foamed gel is injected into a mold and placed in a drying oven for curing under predetermined curing conditions. The pre-set curing temperature and curing time can be adjusted according to actual conditions to obtain a high-quality foam glass embryo.
[0118] According to an embodiment of the present disclosure, the composition of the coal gasification ash includes at least one of the following: SiO2, Al2O3, CaO, Fe2O3. The composition of the coal gasification ash produced by the coal gasification process may be a mixture of SiO2 and Al2O3, a mixture of SiO2, Al2O3 and CaO, a mixture of SiO2, Al2O3 and Fe2O3, or a mixture of SiO2, Al2O3, CaO and Fe2O3, which also includes a small amount of residual carbon. According to an embodiment of the present disclosure, the content of glassy phase substances in the glassy phase slag is greater than 95%.
[0119] The coal gasification ash is transformed into a highly active glass phase slag after being quenched with molten water. The main chemical components are SiO2, Al2O3, CaO and Fe2O3, among which the sum of the contents of SiO2 and Al2O3 is about 70%, and only a small amount of crystalline phase is contained. After the coal gasification ash is melted, the content of glass phase material in the slag is greater than 95%, and this type of glass phase material has high activity and has the ability to undergo hydration reaction with alkaline solution.
[0120] According to an embodiment of the present disclosure, before the glass phase slag is subjected to alkali activation treatment, the process further includes: grinding the glass phase slag to form powdered glass phase slag, thereby increasing the contact area with the alkali-activated solution, facilitating the glass phase slag to be fully mixed with the alkali solution, and accelerating the full progress of the hydration reaction. The particle size of the glass phase slag obtained after grinding is less than 75 μm, for example, it can be 72 μm, 70 μm, 60 μm, 50 μm, 30 μm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0121] In order to make the purpose, technical solution and advantages of the present disclosure clearer and more specific, the technical solution and principle of the present disclosure are further explained below through specific embodiments combined with the accompanying drawings. It should be noted that the following specific embodiments are only used as examples, and the protection scope of the present disclosure is not limited thereto.
[0122] The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. Specific techniques or conditions not specified in the examples are conventional methods and can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions.
[0123] Figure 2 It is a schematic diagram of the operation flow of a method for preparing microcrystalline glass according to another embodiment of the present disclosure.
[0124] The following, combined Figure 2 , exemplified by specific embodiments 1 to 5.
[0125] Example 1
[0126] like Figure 2 As shown, a method for preparing a glass-ceramic according to an embodiment of the present disclosure includes:
[0127] The coal gasification ash is quenched with molten water to obtain glassy slag, which is crushed, ground, and sieved to obtain powdered glassy slag. A 2.5M NaOH aqueous solution is prepared as an alkali-activated solution; polyethylene glycol octylphenyl ether is selected as a surfactant. The addition ratio of powdered glassy slag, alkali-activated solution, and surfactant is 61:35:4wt%.
[0128] The powdered glass phase slag was mixed with a NaOH aqueous solution, and mechanically stirred at a speed of 500 rpm for 3 hours for alkali activation treatment to promote the hydration reaction between the glass phase in the slag and the alkali-activated solution. Then, the pre-curing treatment was carried out at a temperature of 75°C for 60 minutes to form an inorganic gel. The surfactant polyethylene glycol octylphenyl ether was added to the inorganic gel, and the high-speed and vigorous stirring was carried out at a speed of 2000 rpm for 10 minutes for mechanical foaming. Then, the foaming gel was poured into a mold, and after curing at 75°C for 24 hours, the mold was demolded to obtain a foam glass embryo. The foam glass embryo was sintered, heated to 900°C at a rate of 20°C / min, maintained for 2 hours, and then cooled to room temperature to obtain microcrystalline glass.
[0129] The pore size distribution of the microcrystalline glass prepared in Example 1 of the present disclosure is uniform, the porosity is 68.97%, and the compressive strength is 2.00 MPa.
[0130] Example 2
[0131] like Figure 2 As shown, a method for preparing a glass-ceramic according to an embodiment of the present disclosure includes:
[0132] The coal gasification ash is quenched with molten water to obtain glassy slag, which is crushed, ground, and sieved to obtain powdered glassy slag. A 2.5M NaOH aqueous solution is prepared as an alkali-activated solution; polyethylene glycol octylphenyl ether is selected as a surfactant. The addition ratio of powdered glassy slag, alkali-activated solution, and surfactant is 61:35:4wt%.
[0133] The powdered glass phase slag was mixed with a NaOH aqueous solution, and mechanically stirred at a speed of 500 rpm for 3 hours for alkali activation treatment to promote the hydration reaction between the glass phase in the slag and the alkali-activated solution. Then, the pre-curing treatment was carried out at a temperature of 75°C for 90 minutes to form an inorganic gel. The surfactant polyethylene glycol octylphenyl ether was added to the inorganic gel, and the high-speed and vigorous stirring was carried out at a speed of 2000 rpm for 10 minutes for mechanical foaming. Then, the foaming gel was poured into a mold, and after curing at 75°C for 24 hours, the mold was demolded to obtain a foam glass embryo. The foam glass embryo was sintered, heated to 800°C at a rate of 10°C / min, maintained for 2 hours, and then cooled to room temperature to obtain microcrystalline glass.
[0134] The porosity of the microcrystalline glass prepared in Example 2 of the present disclosure is 49.87%, and the compressive strength is 1.60 MPa.
[0135] Example 3
[0136] like Figure 2 As shown, a method for preparing a glass-ceramic according to an embodiment of the present disclosure includes:
[0137] The coal gasification ash is quenched with molten water to obtain glassy slag, which is crushed, ground, and sieved to obtain powdered glassy slag. A 2.5M NaOH aqueous solution is prepared as an alkali-activated solution; polyethylene glycol octylphenyl ether is selected as a surfactant. The addition ratio of powdered glassy slag, alkali-activated solution, and surfactant is 51:45:4wt%.
[0138] The powdered glass phase slag was mixed with a NaOH aqueous solution, and mechanically stirred at a speed of 500 rpm for 3 hours for alkali activation treatment to promote the hydration reaction between the glass phase in the slag and the alkali-activated solution. Then, the pre-curing treatment was carried out at a temperature of 75°C for 120 minutes to form an inorganic gel. The surfactant polyethylene glycol octylphenyl ether was added to the inorganic gel, and the high-speed and vigorous stirring was carried out at a speed of 2500 rpm for 10 minutes for mechanical foaming. Then, the foaming gel was poured into a mold, and after curing at 75°C for 24 hours, the mold was demolded to obtain a foam glass embryo. The foam glass embryo was sintered, heated to 900°C at a rate of 10°C / min, maintained for 2 hours, and then cooled to room temperature to obtain microcrystalline glass.
[0139] The porosity of the microcrystalline glass prepared in Example 3 of the present disclosure is only 16.23%, and the compressive strength is 6.84 MPa.
[0140] Example 4
[0141] like Figure 2 As shown, a method for preparing a glass-ceramic according to an embodiment of the present disclosure includes:
[0142] The coal gasification ash is quenched with molten water to obtain glassy slag, which is crushed, ground, and sieved to obtain powdered glassy slag. A 2.5M NaOH aqueous solution is prepared as an alkali-activated solution; polyethylene glycol octylphenyl ether is selected as a surfactant. The addition ratio of powdered glassy slag, alkali-activated solution, and surfactant is 66:30:4wt%.
[0143] The powdered glass phase slag was mixed with a NaOH aqueous solution, and mechanically stirred at a speed of 500 rpm for 3 hours for alkali activation treatment to promote the hydration reaction between the glass phase in the slag and the alkali-activated solution. Then, the pre-curing treatment was carried out at a temperature of 75°C for 30 minutes to form an inorganic gel. The surfactant polyethylene glycol octylphenyl ether was added to the inorganic gel, and the high-speed and vigorous stirring was carried out at a speed of 2500 rpm for 10 minutes for mechanical foaming. Then, the foaming gel was poured into a mold, and after curing at 75°C for 36 hours, the mold was demolded to obtain a foam glass embryo. The foam glass embryo was sintered, heated to 900°C at a rate of 5°C / min, maintained for 2 hours, and then cooled to room temperature to obtain microcrystalline glass.
[0144] The porosity of the microcrystalline glass prepared in Example 4 of the present disclosure is 44.75%, and the compressive strength is 7.49 MPa.
[0145] Example 5
[0146] like Figure 2 As shown, a method for preparing a glass-ceramic according to an embodiment of the present disclosure includes:
[0147] The coal gasification ash is quenched with molten water to obtain glassy slag, which is crushed, ground, and sieved to obtain powdered glassy slag. A 2.5M NaOH aqueous solution is prepared as an alkali-activated solution; polyethylene glycol octylphenyl ether is selected as a surfactant. The addition ratio of powdered glassy slag, alkali-activated solution, and surfactant is 56:40:4wt%.
[0148] The powdered glass phase slag was mixed with a NaOH aqueous solution, and mechanically stirred at a low speed of 500 rpm for 3 hours for alkali activation treatment to promote the hydration reaction between the glass phase in the slag and the alkali-activated solution. Then, the pre-curing treatment was carried out at a temperature of 75°C for 30 minutes to form an inorganic gel. The surfactant polyethylene glycol octylphenyl ether was added to the inorganic gel, and the high-speed and vigorous stirring was carried out at a speed of 2500 rpm for 10 minutes for mechanical foaming. Then, the foaming gel was poured into a mold, and after curing at 75°C for 48 hours, the mold was demolded to obtain a foam glass embryo. The foam glass embryo was sintered, heated to 1000°C at a rate of 5°C / min, maintained for 2 hours, and then cooled to room temperature to obtain microcrystalline glass.
[0149] The porosity of the microcrystalline glass prepared in Example 5 of the present disclosure is 41.38%, and the compressive strength is 4.86 MPa.
[0150] The disclosed embodiment obtains glass-rich slag by subjecting gasification slag to a molten water quenching treatment, and combines alkali activation treatment, pre-curing treatment, mechanical foaming treatment and sintering treatment to effectively convert and utilize organic carbon in waste containing glass phase. The process has strong operability, and fully utilizes the activation and modification of minerals in coal gasification ash by the melting process to transform inorganic minerals into high-value-added microcrystalline glass. The sintering temperature is low, which effectively reduces energy consumption and realizes large-scale disposal and resource utilization of coal gasification slag.
[0151] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A method for preparing glass-ceramics, comprising: The coal gasification ash is quenched with molten water to obtain glass phase slag; Performing an alkali activation treatment on the glass phase slag to obtain a monomer suspension containing a predetermined type of monomer; Pre-curing the monomer suspension to obtain an inorganic gel; Performing mechanical foaming treatment on the inorganic gel to obtain a foamed gel; Putting the foaming gel into a mold and curing the foaming gel under predetermined curing conditions to obtain a foamed glass embryo; The foam glass embryo is sintered to obtain glass-ceramics.
2. The method according to claim 1, wherein: The alkali activation treatment of the glass phase slag comprises: The glassy slag is placed in an alkali-activated solution, so that a portion of the glassy slag undergoes a hydration reaction in the alkali-activated solution to generate the monomer suspension, wherein the monomer suspension includes the predetermined type of monomer and unreacted slag particles.
3. The method according to claim 2, wherein: The alkaline excitation solution is a NaOH aqueous solution; The predetermined type of monomers at least includes: calcium aluminosilicate hydrate monomers and sodium aluminosilicate hydrate monomers.
4. The method according to claim 2, after placing the glass phase slag in an alkali-activated solution, further comprises: The base-excited solution is stirred under first predetermined stirring conditions.
5. The method according to claim 4, wherein: The first predetermined stirring condition includes: The first stirring speed is: 300-500 rpm; The first stirring time is: 1 to 4 hours.
6. The method according to claim 2, wherein: The pre-curing treatment of the monomer suspension comprises: The monomer suspension is placed in a drying oven, and the predetermined type of monomer in the monomer suspension is subjected to a polycondensation reaction to generate a polycondensate under predetermined curing conditions, and the unreacted slag particles are wrapped by the polycondensate to obtain the inorganic gel.
7. The method according to claim 6, wherein: The predetermined curing conditions include: Curing temperature: 70~80℃; Curing time: 30 to 120 minutes.
8. The method according to claim 1 or 2, wherein the inorganic gel is subjected to mechanical foaming treatment to obtain the foamed gel, comprising: A surfactant is added to the inorganic gel, and the inorganic gel and the surfactant are mixed under a second predetermined stirring condition, so that the inorganic gel is mechanically foamed under stirring and the action of the surfactant to obtain the foamed gel.
9. The method according to claim 8, wherein: The surfactant is polyethylene glycol octylphenyl ether.
10. The method according to claim 8, wherein the second predetermined stirring condition comprises: The second stirring speed is: 1800-2500 rpm; The second stirring time is 10 to 15 minutes.
11. The method according to claim 8, wherein: The mass contents of the glass phase slag, the alkali activated solution, and the surfactant are respectively: Glass phase slag: 51~66Wt%. Alkali excitation solution: 30-45Wt%; Surfactant: 3-5 wt%.
12. The method according to claim 1, wherein: The step of sintering the foam glass embryo to obtain glass-ceramics includes: Heating the foam glass embryo to a predetermined sintering temperature at a predetermined heating rate; The glass-ceramics is obtained by sintering the foam glass embryo according to the predetermined sintering temperature.
13. The method according to claim 12, wherein: The predetermined heating rate is: 5-20°C / min; The predetermined sintering temperature is 700-1000°C.
14. The method according to claim 1, wherein: The predetermined maintenance conditions include: Curing temperature: 70~80℃; The curing time is: 12 to 48 hours.
15. The method of claim 1, wherein: The components of the coal gasification ash include at least one of the following: SiO2, Al2O3, CaO, Fe2O3.
16. The method of claim 1, wherein: In the glassy slag, the content of glassy substances is greater than 95%.
17. The method according to claim 1, before subjecting the glass phase slag to alkali activation treatment, further comprising: The glass phase slag is ground.
18. The method of claim 17, wherein: The particle size of the glassy slag obtained after grinding is less than 75 μm.
